Psychiatric and Developmental Effects of Isotretinoin (Retinoid) Treatment for Acne Vulgaris - Alessandra Suuberg, JD (Elsevier, 2019)
ABSTRACT: Background: An association between isotretinoin (13-cis-retinoic acid, sold under trade names including Accutane [Hoffmann-La Roche Inc, Basel, Switzerland]) and birth defects, depression, and suicide is well documented but controversial. A link to psychosis and exacerbation of bipolar symptoms is less extensively addressed in the literature. Objective: Given recent conceptualization of psychotic disorders as neurodevelopmental, and current interest in possible shared etiology of different neurodevelopmental disorders such as psychosis, autism, and intellectual disability, this review concurrently examines the literature on developmental (primarily teratogenic) and psychiatric side effects of isotretinoin exposure. The goal of concurrent review is to identify shared mechanisms in the literature that may inform future efforts to clarify the neurocognitive and psychiatric effects of isotretinoin exposure at different developmental stages or given different genetic backgrounds. Methods: Literature was obtained by PubMed search for the term isotretinoin in combination with each of the terms psychosis, psychiatric, and teratogenic. Resulting articles met inclusion criteria for review if they addressed psychiatric side effects of isotretinoin treatment or the neurobehavioral teratology of isotretinoin. Results: The association of isotretinoin exposure with prenatal developmental toxicity is well established. Although numerous reports also link isotretinoin treatment with psychiatric side effects, this association remains controversial. Conclusions: The extent to which isotretinoin influences pediatric and adult development and cognition, and whether and why certain individuals may be susceptible to psychiatric side effects, remains to be clarified. Curr Ther Res Clin Exp. 2019; 80:XXX-XXX) Key words: acne vulgaris, depression, isotretinoin, psychosis, retinoid, suicide